PERSEPSI SISWA TENTANG KEMAMPUAN MENGAJAR GURU DAN MOTIVASI BELAJAR SISWA DENGAN PRESTASI BELAJAR EKONOMI - Nagara, Erliza Septia; Trisnawati, Trisnawati (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2019)
Abstract Learning achievement is the result of a person or student who is obtained after taking a test that can be seen in the form of numbers or values. Good learning achievement is expected by all parties, not only students but also teachers and parents. Good learning achievement is the result of the absorption of good lessons. Absorption of good lessons is supported by students' perceptions of teacher teaching abilities and good learning motivation. This study aims to determine the relationship between students 'perceptions of teacher teaching abilities and learning motivation with students' economic learning achievement.Â  The method used is ex post facto, with the level of explanatory research classified as associative research, sample design is probability sampling, sampling used is simple random sampling using the T-Yamane formula, testing hypotheses using product moment correlation statistics. Based on statistical tests using product moment correlation is known:Â  First, there is a relationship between students 'perceptions of the teacher's teaching ability and students' learning motivation. Second, there is a relationship between students 'learning motivation and students' economic learning achievement.